ELECTRON MICROSCOPIC STATE OF THE KIDNEY IN EXPERIMENTAL TRAUMA AND ISCHEMIA - Boris, R.M. (World of Medicine and Biology, 2013)
In the experiment on white rats ultrastructural changes of the kidneys in multiple trauma and ischemia were studied. In the experiment dynamics it was revealed that the epithelium destructive changes of proximal and distal tubules of the nephrons were accompanied with microcirculatory disorders in the capillaries of the renal glomeruli and the peritubular network. Such changes have negative impact on the kidney functionality, disturb phases of urine formation.
Keywords: kidney; electron microscopic changes; multiple trauma and ischemia